Teachers as Strategic Agents in Multicultural Education at Vocational High Schools: An Analysis of Practice at SMKN 1 Talamau - Refinal; Ismaiza Busti; Julhadi; Muhammad Youssef Al Deek (Walidem Institute and Publishing, 2026)
Objective: Analyze the strategic role of teachers in the implementation of multicultural education in vocational schools with a focus on SMKN 1 Talamau. The study highlights the role of teachers in the formation of the inclusive character and social competence of students. The results are directed at the formulation of contextual recommendations for the role of teachers. Theoretical framework: This research is based on the concept of multicultural education that emphasizes the management of diversity in learning. Teachers are positioned as strategic actors in building critical cultural awareness. Multicultural education is understood as part of the formation of character and work readiness of vocational school students. Literature review: The study of multicultural education is still dominated by the context of general and urban education. Studies on the role of teachers in vocational schools and regional schools are still limited. In addition, the role of teachers is generally studied descriptively and not yet strategically. Methods: This study uses a qualitative approach with an analytical descriptive design. Data were collected through in-depth interviews, participatory observations, and documentation studies at SMKN 1 Talamau. Data analysis is carried out thematically by ensuring validity through triangulation. Results: The results of the study show that the role of teachers as role models, facilitators, innovators, mediators, and reflective evaluators is the main pillar of multicultural education. Effective implementation occurs when multicultural values are integrated into the curriculum, learning, and school culture. This role contributes to strengthening students' inclusive character and social competence. Implications: The development of multicultural education in vocational schools requires the support of school policies, teacher competency improvement, and government regulations. The sustainability of implementation depends on cross-stakeholder collaboration. The sustainability of implementation depends on cross-stakeholder collaboration. Novelty: The novelty of this research lies in the analysis of the strategic and multidimensional role of teachers in the context of regional vocational schools. This study integrates multicultural education with vocational education as well as the needs of the world of work through contextual and adaptive conceptual models.